Pengaruh Store Environment Perception pada Interior Toko Sociolla terhadap Dorongan Perilaku Impulsive Buying - Sugiharto, Chavela Angelica Putri; Lauwinata, Jesslyn Natalie; Yosevina, Christiana Terecia; Yudianto, Bernardinus Realino (Kajian Branding Indonesia, 2025)
This study aims to analyze how perceptions of the store environment can encourage customers’ impulse buying behavior, and what factors influence impulse buying. Also, to analyze how individual characteristics can influence these purchases. The research method used is quantitative research by distributing questionnaires online, using a Likert scale of 1-5. The research was found that impulsive buying tendency and layout had the strongest effect on urge to buy impulsively. maintain a positive store environment and add other strategies to stimulate customer’s tendency that leads to urge to buy impulsively.